Reevaluation of Chloropseudomonas ethylica Strain 2-K - GRAY, B. H.; FOWLER, C. F.; NUGENT, N. A.; RIGOPOULOS, N.; FULLER, R. C. (International Journal of Systematic and Evolutionary Microbiology, 1973)
Cultures of Chloropseudom onas ethylica strain 2-K obtained from several laboratories were examined. All cultures examined to date in this laboratory contained nonmotile, green, photosynthetic bacteria (Chlorobiaceae) identical to published descriptions of Chlorokium limicola and at least one colorless, motile bacterium. All attempts to isolate motile photosynthetic bacteria corresponding to published descriptions of C. ethylica from such cultures have been unsuccessful. Several physiological characteristics previously ascribed to C. ethylica 2-K are expressions of mixed cultures rather than the property of a single species.